Cost and Utilization Outcomes of Pharmacist-Led Medication Therapy Optimization in a Medicare ACO Population - Hazem F Elewa; Joseph F Levy; Chintan Pandya; Steven E Goldberg; Travis A Morgan (Health Affairs Scholar, 2026)
Abstract Introduction Medication-related problems are a persistent source of avoidable spending among Medicare beneficiaries, presenting an important opportunity to improve the quality of care for seniors and reduce financial burden on the Medicare program. Methods We evaluated a pharmacist-led medication therapy optimization (MTO) program implemented in a Medicare accountable care organization population using a regression-adjusted difference-in-differences design with propensity score matching. The analysis included 1,003 treated members and 14,031 matched controls contributing 334,531 member-months of claims data (2022–2025). The MTO program combined pharmacogenomic testing, a nine-vector medication-risk algorithm, comprehensive pharmacist review, and structured recommendations to prescribers. Results MTO participation was associated with a statistically significant reduction in total medical costs (pooled average treatment effect on the treated: −19.4%, −$246 per member per month [PMPM]; p<0.001). The treatment effect was strongly duration-dependent, growing from −4.7% in the first three months to −31.9% (−$462 PMPM; p<0.001) beyond nine months of program benefit. All care settings showed significant reductions: inpatient admissions −43.1% (p<0.001), emergency department visits −41.3% (p<0.001), and outpatient visits −28.3% (p<0.001). Conclusion Parallel trends validation and a pronounced dose-response relationship support a causal interpretation. Short-duration evaluations are likely to substantially underestimate the full economic value of an MTO program.